Human development and economic growth in Asia: a dynamic panel cointegration and causality analysis. (23rd April 2019) - Abedin, Md. Thasinul; Sen, Kanon Kumar; Hossain, Md. Sharif
This paper explores the impact of human development on economic growth in a large Asian panel, covering more than 83% of the entire Asian economy, by using data from 1990 to 2014 for each country. In this paper, the growth model considering human development unlike Malthusian and Neoclassical views is augmented with other key macroeconomic variables namely per capita electricity consumption and capital formation to represent a hyperopic view of impact on economic growth. Human development has significant positive impact on economic growth both in the short-run and in the long-run like that of electricity consumption and capital formation. However, fertility has significant negative impact on economic growth in the short-run unlike that of the long-run. Imbalance in economic growth takes approximately 9.5 years to adjust. Innovation in human development makes economic growth respond slightly positively in next 8 years and explains a part of variation in economic growth.